GOOD TO GREAT: WHY SOME COMPANIES MAKE THE LEAP…AND SOME OTHERS DON’T - Jim Collins; Reviewed by: Zaenuddin Hudi Prasojo (Al-Albab, 2012)
The book consists of nine chapters explaining the concept of Good to Great. Starting from emphasizing that “good is the enemy of great”, Jim Collins provides great explanations as well as arguments of why his concept is very important for leaders who want to be successful in their efforts of building “enduring results” of their companies, organizations, or institutions. He in detail explains four principles underlining the framework of good to great. There are disciplined people (level 5 leadership and first who, then what concepts), disciplined thought (confront the brutal facts and the Hedgehog concepts), disciplined action (culture of discipline and the flywheel concepts), and building greatness to last (clock building, not the time telling and preserve the core/stimulate progress concepts). For further analysis of the Good to Great, I will shortly summarize the concept of how to make something good to be great explained in the book in the following section. I will also conclude this paper by commenting on the concept as my critique toward the theory of Good to Great.